2015
DOI: 10.1044/2015_jslhr-l-14-0250
|View full text |Cite|
|
Sign up to set email alerts
|

Grammatical Planning Units During Real-Time Sentence Production in Speakers With Agrammatic Aphasia and Healthy Speakers

Abstract: Purpose: Grammatical encoding (GE) is impaired in agrammatic aphasia; however, the nature of such deficits remains unclear. We examined grammatical planning units during real-time sentence production in speakers with agrammatic aphasia and control speakers, testing two competing models of GE. We queried whether speakers with agrammatic aphasia produce sentences word by word without advanced planning or whether hierarchical syntactic structure (i.e., verb argument structure; VAS) is encoded as part of the advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 50 publications
5
37
0
4
Order By: Relevance
“…These findings suggest that agrammatic speakers do form abstract structural representations, including thematic representations, that guide sentence production, and are thus inconsistent with representational accounts of sentence production deficits (Friedmann & Grodzinsky, 1997). In contrast, they lend support to grammatical encoding accounts of agrammatism, and in particular are consistent with research suggesting that agrammatic speakers have intact access to thematic and syntactic information but difficulty implementing this information as sentence production unfolds (Cho & Thompson, 2010; Lee & Thompson, 2011a, 2011b; Lee et al, 2015). …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings suggest that agrammatic speakers do form abstract structural representations, including thematic representations, that guide sentence production, and are thus inconsistent with representational accounts of sentence production deficits (Friedmann & Grodzinsky, 1997). In contrast, they lend support to grammatical encoding accounts of agrammatism, and in particular are consistent with research suggesting that agrammatic speakers have intact access to thematic and syntactic information but difficulty implementing this information as sentence production unfolds (Cho & Thompson, 2010; Lee & Thompson, 2011a, 2011b; Lee et al, 2015). …”
Section: Discussionsupporting
confidence: 81%
“…They also have difficulty producing syntactically complex sentences such as passives and embedded clauses (Caplan & Hanna, 1998; Cho-Reyes & Thompson, 2012; Faroqi-Shah & Thompson, 2003). On some theories, agrammatic sentence production deficits stem from an underspecification of linguistic representations (Friedmann & Grodzinsky, 1997), precluding the ability to generate fully-specified grammatical sentences, whereas other accounts link these deficits to impaired grammatical encoding, i.e., inability to implement grammatical representations in real-time (Cho & Thompson, 2010; Lee, Yoshida, & Thompson, 2015; Linebarger, Schwartz, Romania, Kohn, & Stephens, 2000). …”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that measuring speakers’ viewing times is informative in studies examining the time course of lexical access in individuals with aphasia, particularly those whose naming latencies might be difficult to obtain due to frequently co-occurring motor speech disturbances (Dell et al, 1997; Schwartz et al, 2006). These are novel findings indicating that monitoring eye gaze during controlled naming tasks may overcome this methodological limitation and can provide another sensitive measure for investigating online lexical access (see also Odekar, Hallowell, Kruse et al, 2009 for semantic facilitation effects on eye movement patterns during semantic association tasks in healthy young adults and Lee & Thomson, 2011a, 2011b; Lee, Yoshida, & Thompson, submitted for using eye movements for studying on-line processes of sentence production in agrammatic aphasia).…”
Section: Discussionmentioning
confidence: 95%
“…Recent eyetracking sentence production studies have shown that access of verb argument structure information before speech onset is facilitative of sentence production in IWA, in line with structure-driven production (Lee & Thompson, 2011a;2011b;Lee, Yoshida, & Thompson, 2015). However, it remains an open question if the aphasic language production system also follows word-driven incremental production, opportunistically using wordbased cues to ease syntactic production.…”
Section: Introductionmentioning
confidence: 99%